Effects of Stocking Density on Production Performance of nile Tilapia (Oreochromis niloticus) in grow-out Culture Cages - Awal Hossain, Md Robiul; Hosain, Md Eilious; Tabassum, Anika; Naser, Md Niamul (Bangladesh Journal of Zoology, 2022)
A 120-day cage grow-out production performance of Nile Tilapia, Oreochromis niloticus was conducted in the Dakatia river, Echoli, Chandpur to identify an optimal stocking density. The three stocking densities were used at 30, 50, and 70 tilapia m-3 under three treatments with triplicate. The initial average weight of tilapia fingerlings at 32.31±9.59 g was stocked. Final weight, specific growth rate, and survival were significantly (p < 0.05) higher in the 30 tilapia m-3 stocking density than those in the 50 and 70 tilapia m-3 stocking densities. The best food conversion ratio of 1.47 was found in the 30 tilapia m-3 stocking density and followed by 2.0 and 2.90 in the 50 and 70 tilapia m-3 stocking densities, respectively. The production was comparable (p > 0.05) between the 50 and 70 tilapia m-3 stocking densities; however, the net profit was higher (p < 0.05) in the 50 tilapia m-3 stocking density group compared to the two other stocking density groups. This study suggests a stocking of density at 50 tilapia m-3 to increase Nile Tilapia O. niloticus productivity in the riverine cage culture system. Bangladesh J. Zool. 50 (2): 239-250, 2022